Competition between polymers for adsorption on silica a solvent relaxation NMR and small-angle neutron scattering study - Cooper, Catherine L (Langmuir : the ACS journal of surfaces and colloids, 2013)
The competition between poly(vinylpyrrolidone) and poly(ethylene oxide) for adsorption at the silica surface was studied by solvent relaxation nuclear magnetic resonance and small-angle neutron scattering. The additive nature of the NMR relaxation rate enhancement was used to observe changes in the train layer when the two polymers were in direct competition for an increasing weight percentage of silica. PVP is shown to displace preadsorbed PEO from the particle surface, and this was observed for a range of PVP molecular weights. SANS measurements were found to give detailed information on the adsorption of the polymers in the separate systems; however, only qualitative information on the adsorption of the polymers could be obtained from the mixed samples. At a total polymer concentration of 0.4% w/v with 1.1% w/v silica, the SANS data were consistent with PVP adsorbing at the surface and dPEO remaining in solution, in agreement with the NMR data